KARAKTERISTIK PEMANEN DAYA LISTRIK BERBASIS GETARAN STRUKTUR - La Ode Ahmad Barata; Samhuddin Samhuddin (Jurnal Rekayasa Mesin, 2022)
Mechanical vibration is a potential source of micro-electrical energy harvesting mechanisms for micro electrical power supply for IoT system networks, wireless and sensors where the power requirements are relatively lower and available independently. In this study, the characteristics of the cylinder vibration response as a trigger for energy harvesting from flow-induced vibrations at various air velocities were investigated experimentally in a wind tunnel test section. Harvesting of micro power from cylinder’s motion by using galfenol (Fe-Ga) material was also investigated simultaneously. The maximum cylinder’s vibration response was obtained by using the plain cylinder model. Cylinder taper variation reduce the maximum vibration response. The position of the major (D) and minor (d) (or inverse position) diameters also affects the vibration response. However, tapering the cylinder reduces the onset vibration with respect to the flow velocity. The frequency of the vortex (Strouhal, St) ranges from 0.25 to 0.12. The minor diameter of the tapered cylinder has the effect on decreasing the vibration response and tends to be stationary. Minor diameter reduction reduces the potential for vibration to the structure. The maximum power generated by the test model is about 8.5 mW with the power RMS value of 2.3 mW and power coefficient about 4%.